Diplomado en Simulación Gerencial y Responsabilidad Social Empresarial-Equipo Alfa-mundo 2 (2022)
The Diploma in Management Simulation and Corporate Social Responsibility arises from an alliance between Universidad El Bosque and the company Company Game, which gives us the possibility of using the Business Global simulator, allowing us to plan and make decisions from the managerial field within 4 areas such as: logistics, marketing, finance, and human resources. Within the process of developing the activity of the diploma course, we sought to apply the knowledge acquired throughout the degree, to make decisions that will have a positive impact on the growth of a company. For the development of the exercise, we were appointed Alfa, which is dedicated to the production and marketing of global consumer products such as small appliances, home automation and personal technology, has its headquarters in Germany and operated within the markets of the Western European Union and Russia and non-EU European countries. Therefore, as a group we made four decisions corresponding to the four learning modules seen in the development of the simulator and that were mentioned above, making the company grow in all the aspects raised at the beginning. Based on the decision making and the analysis of the respective results obtained, this report arises, which will be presented jointly to the evaluators of the diploma course, who will generate feedback where the practice, execution and commissioning will finally be evaluated. progress of the knowledge achieved after the completion of the same.